Long-term opioid therapy for chronic noncancer pain: second update of the German guidelines - Petzke, Frank; Bock, Frietjof; Hüppe, Michael; Nothacker, Monika Judith; Norda, Heike; Radbruch, Lukas; Schiltenwolf, Marcus; Schuler, Matthias; Tölle, Thomas R.; Viniol, Anika; Häuser, Winfried (Pain reports, 2020)
Introduction:  - The opioid epidemic in North America challenges national guidelines worldwide to define the importance of opioids for the management of chronic noncancer pain (CNCP). - Methods:  - The second update of the German guidelines on long-term opioid therapy for CNCP was developed by 26 scientific associations and 2 patient self-help organizations. A systematic literature search in CENTRAL, Medline, and Scopus (to May 2019) was performed. Meta-analyses of randomized controlled trials and open-label extension studies with opioids for CNCP were conducted. Levels of evidence were assigned according to the Oxford Centre for Evidence-Based Medicine classification system. The formulation and strength of recommendations were established by multistep formalized procedures to reach a consensus according to German Association of the Medical Scientific Societies regulations. The guidelines underwent external review by 4 experts and public commentary. - Results:  - Opioids are one drug-based treatment option for short- (4-12 weeks), intermediate- (13-26 weeks), and long-term (>26 weeks) therapy of chronic pain in osteoarthritis, diabetic polyneuropathy, postherpetic neuralgia, and low back pain. Contraindications are primary headaches, functional somatic syndromes, and mental disorders with the (cardinal) symptom of pain. For specified other clinical pain conditions, short- and long-term therapy with opioids should be evaluated on an individual basis. Long-term therapy with opioids is associated with relevant risks. - Conclusion:  - Responsible application of opioids requires consideration of possible indications and contraindications, as well as regular assessment of clinical response and adverse effects. Neither uncritical opioid prescription nor general rejection of opioids is justified in patients with CNCP.